Business models for smart local energy systems—A triple layered perspective - Pappas, Dimitrios; Braunholtz-Speight, Timothy; Hannon, Matthew; Webb, Janette; Fuentes González, Fabián; Sharmina, Maria (Frontiers in Sustainable Energy Policy, 2023)
Smart and local energy systems (SLES) offer an alternative to large-scale energy provision and a boost to the transition towards a low-carbon economy. To establish workable business models, the Business Model Canvas (BMC) is a tool increasingly used to analyse SLES. However, the framework does not adequately describe the multiple value streams that can characterise the business models of many SLES projects. The decarbonisation, digitalisation and democratisation associated with SLES, mean their value proposition extends beyond straightforward economic value and towards environmental and social value. As such, we argue that the triple-layered BMC, which incorporates the environmental and social layers into its analysis, better reflects real-world business model complexity. We modify and use the triple-layered BMC to analyse 18 SLES projects around the world, and we find a wide reporting gap of environmental and social elements. We provide a common framework to SLES stakeholders for identifying and adding environmental and social value to their business models.